(untitled) (The Journal of Plant Protection Sciences, 2020)
Mankind has a history of using crop protection products from non-selective, naturally occurring compounds to highly specific synthetic and biological materials for assured food production and protection of environment since long time. There is a sequential rise in the production and consumption of pesticides in India during the last three decades. Researches are going on to develop safer molecules which could undergo photo-degradation, microbial degradation as well as chemical degradation leaving very less amount of residues in the environment. Conventional pesticide formulations like WP, EC etc are endangering human health and polluting environment. Newly developed modern formulations like water emulsifiable gel, floating granules, drift less dust, macro and micro encapsulated suspension, hollow fibers, monolithic matrix, laminated structures etc can avoid these problems. The prime motto for these developments is to give protection to the crops along with safety to the natural enemies of different pests as a whole safety to environment.